In situ assessment of the fabric and energy performance of five conventional and non-conventional wall systems using comparative coheating tests. (15th November 2016) - Latif, Eshrar; Lawrence, Mike; Shea, Andy; Walker, Pete
Abstract: Comparative coheating tests have been carried out in five test buildings with walls constructed of Concrete Block Masonry and timber framed Hemp-lime composite, Polyisocyanurate (PIR), Wood Fibre and Mineral Wool. Five different methods of determining heat loss coefficient (HLC) were applied during the data analysis. While some variability in HLC values was observed between the different forms of construction, the hierarchy of HLC values among the test buildings were consistent, with the Concrete Block Masonry exhibiting the highest and Wood Fibre test building exhibiting the lowest HLC values. Except for the Concrete Block Masonry, there was good agreement between the calculated HLC values and those derived by applying the method 5 where the analysis incorporated both the effects of solar radiation and thermal mass. The in-situ U-value for the Concrete Block wall, determined by the average method, was 32.8% higher than its design value, whilst the other wall systems showed marginally lower U-values than their corresponding design U-values. Highlights: Test buildings of different wall systems are compared by coheating tests. Five methods applied to analyse the coheating data. Masonry wall exhibited the highest deviation from the design U-value. Except for masonry, heat loss coefficients, U-values of the systems are similar. Heat loss coefficient values can differ based on the methods applied.